Aplikasi Profil Perusahaan Digital Berbasis Web - Ire Puspa Wardhani; Annisa Mutia Putri; Susi Widayati (Sekolah Tinggi Teknik - PLN, 2019)
Alternatives to promoting companies with a variety of products, besides being able to reduce paper use which has an impact on promotion costs, and creating a wider market, are the main reasons why this research was conducted. There are two types of websites that can be used in business development, namely online store websites and company profile websites. The purpose of digital company profiles is to display company profiles and build credibility in cyberspace. Digital company profile does not bring revenue directly like online store websites, but digital website-based company profiles become a more accurate and trusted source of information. Through a digital company profile, a better business image can be built and entrepreneurs can show the world that the goods and products offered are of good quality. This digital company profile is a promotional media campaign that is more effective and efficient. Website-based Digital Company Profile application, as a means of promotion, is made with the Design and Development of Multimedia Systems that integrate its components. The end result of this application is in the form of files that can be applied in the form of a disk and uploaded on the website.